DSIF modulates RNA polymerase II occupancy according to template G + C content. Issue 3 (27th July 2022) - Deng, Ning; Zhang, Yue; Ma, Zhihai; Lin, Richard; Cheng, Tzu-Hao; Tang, Hua; Snyder, Michael P; Cohen, Stanley N
Abstract: The DSIF complex comprising the Supt4h and Supt5h transcription elongation proteins clamps RNA polymerase II (RNAPII) onto DNA templates, facilitating polymerase processivity. Lowering DSIF components can differentially decrease expression of alleles containing nucleotide repeat expansions, suggesting that RNAPII transit through repeat expansions is dependent on DSIF functions. To globally identify sequence features that affect dependence of the polymerase on DSIF in human cells, we used ultra-deep ChIP-seq analysis and RNA-seq to investigate and quantify the genome-wide effects of Supt4h loss on template occupancy and transcript production. Our results indicate that RNAPII dependence on Supt4h varies according to G + C content. Effects of DSIF knockdown were prominent during transcription of sequences high in G + C but minimal for sequences low in G + C and were particularly evident for G + C-rich segments of long genes. Reanalysis of previously published ChIP-seq data obtained from mouse cells showed similar effects of template G + C composition on Supt5h actions. Our evidence that DSIF dependency varies globally in different template regions according to template sequence composition suggests that G + C content may have a role in the selectivity of Supt4h knockdown and Supt5h knockdown during transcription of gene alleles containing expansions of G + C-rich repeats.